2007
DOI: 10.1007/s11205-007-9139-x
|View full text |Cite
|
Sign up to set email alerts
|

Morningness–Eveningness and Satisfaction with Life

Abstract: Biological rhythms, Circadian type, Composite Scale of Morningness, Diurnal preference, Morningness, Personality, Satisfaction with life, Well-being,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 32 publications
6
36
0
Order By: Relevance
“…We highlight the positive association between rMEQ scores and emotional repair, a dimension considered as a good predictor of subjective wellbeing (Chico-Librán et al, 2011;Fernández-Berrocal et al, 2004;Landa et al, 2010;Salguero et al, 2012). In this case, higher morningness scores are linked to a higher ability for emotional repair and, consequently, for subjective well-being, as previous studies have shown by using different measurement instruments (Biss & Hasher, 2012, Jankowski, 2012Lázar et al, 2012;Randler, 2008). The sex differences shown are in agreement with previous data (Fernández-Berrocal & Extremera, 2008;Ruiz et al, 2012;Thayer et al, 2003).…”
Section: Discussionsupporting
confidence: 63%
“…We highlight the positive association between rMEQ scores and emotional repair, a dimension considered as a good predictor of subjective wellbeing (Chico-Librán et al, 2011;Fernández-Berrocal et al, 2004;Landa et al, 2010;Salguero et al, 2012). In this case, higher morningness scores are linked to a higher ability for emotional repair and, consequently, for subjective well-being, as previous studies have shown by using different measurement instruments (Biss & Hasher, 2012, Jankowski, 2012Lázar et al, 2012;Randler, 2008). The sex differences shown are in agreement with previous data (Fernández-Berrocal & Extremera, 2008;Ruiz et al, 2012;Thayer et al, 2003).…”
Section: Discussionsupporting
confidence: 63%
“…Randler finds a significant positive correlation between "morningness" tendencies of people and satisfaction in life [7], and Monk [16] find that MT individuals appear to have more regular lifestyle than ETs. A positive correlation between eveningness and depression level is reported by Hasler et al [17].…”
Section: Sociology and Cronobiologymentioning
confidence: 99%
“…Geographic closeness generally leads to similarity of climate and culture, which helps eliminate confounding factors that may lead to differences in lifestyle behaviors unrelated to city size. In contrast to traditional research investigating lifestyle patterns, where data collection methods include questionnaires and telephone interviewing [6], [7], [8], we leverage data from social media to make inferences about people's lifestyles. The wide adoption of social media brings researchers a new opportunity of studying natural, unconstrained human behavior at very large scales.…”
Section: Introductionmentioning
confidence: 99%
“…Late chronotypes are more likely to have psychiatric illnesses, such as attention-deficit/hyperactivity disorder (ADHD) (Rybak et al, 2007), depressive symptoms (Chelminski et al, 1999), bipolar disorder (Soreca et al, 2009), sleeping difficulties (Giannotti et al, 2002;Ong et al, 2007), and according to one study, also lower sleep efficiency as assessed by actigraphy (Lehnkering et al, 2007). In contrast, early chronotypes exhibit a healthier life style (Wittmann et al, 2006), such as healthier dietary habits (Fleig et al, 2009), and report a higher life satisfaction (Randler, 2008).…”
Section: Introductionmentioning
confidence: 99%